Financial Inclusion and the Role of the Post Office - Anson, Jose; Berthaud, Alexandre; Klapper, Leora; Singer, Dorothe (World Bank, Washington, DC, 2014)
Given their widespread presence in rural and poor areas, post offices can play a leading role in advancing financial inclusion. Yet little is known about the type of clients that post offices reach through their financial service offerings as compared with clients of traditional financial institutions (such as commercial banks). This paper documents and analyzes account ownership patterns at post offices in comparison with traditional financial institutions, using the Global Financial Inclusion Indicators (Global Findex) database, which collects data on account ownership at post offices in 60 countries where postal accounts are offered. Controlling for a host of individual characteristics and country fixed effects, the paper finds that post offices are relatively more likely than traditional financial institutions to provide accounts to individuals who are most likely to be from financially vulnerable groups, such as the poor, less educated, and those out of the labor force. The paper also uses data from the Universal Postal Union to explore the degree to which different postal business models and the size of the postal network help explain differences in account ownership patterns. The results suggest that post offices can boost account ownership by acting as cash-merchants for transactional financial services, such as electronic government and remittance payments, and that partnerships between the post office and other financial institutions coincide with a higher bank account penetration. The paper also finds that the size of the postal network matters; the larger the network-relative to the network of traditional financial institutions -- the more likely it is that adults have an account at the post office.